2022
DOI: 10.3390/ijms23031562
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Apoptosis Pathways and Factors in Oral Squamous Cell Carcinoma

Abstract: Oral cancer is the most common form of head and neck squamous cell carcinoma (HNSCC) and most frequently presents as oral squamous cell carcinoma (OSCC), which is associated with an alarmingly high mortality rate. Internationally, a plethora of research to further our understanding of the molecular pathways related to oral cancer is performed. This research is of value for early diagnosis, prognosis, and the investigation of new drugs that can ameliorate the harmful effects of oral cancer and provide optimal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 140 publications
0
24
0
Order By: Relevance
“…There is much evidence that suggests the human papilloma virus (HPV16) as a risk factor for oropharyngeal cancer [ 10 , 11 , 12 ]. The reported profile in India is not consistent with the global statistics reporting the incidence of HPV in oral cancer to range from 0 to 75% [ 11 , 12 , 13 , 14 ]. However, a study done among the local population with OSCC has shown none of the tumor specimens to be HPV positive [ 15 ].…”
Section: Introductionmentioning
confidence: 68%
“…There is much evidence that suggests the human papilloma virus (HPV16) as a risk factor for oropharyngeal cancer [ 10 , 11 , 12 ]. The reported profile in India is not consistent with the global statistics reporting the incidence of HPV in oral cancer to range from 0 to 75% [ 11 , 12 , 13 , 14 ]. However, a study done among the local population with OSCC has shown none of the tumor specimens to be HPV positive [ 15 ].…”
Section: Introductionmentioning
confidence: 68%
“…Oral cancer is becoming a global health problem due to its relatively high incidence and mortality. Also, due to the poor prognosis of OSCC after surgery combined with chemoradiotherapy (29,30), increasing research studies have paid more attention to the identification of efficient prognostic predictors in OSCC such as microRNA levels (31), long noncoding RNAs (32), and apoptosis-related genes (33). Although the role of pyroptosis in human cancers have been studied, their prognostic values in many other malignancies have not been well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Akt is a protein that plays an important role in survival and induction of cell proliferation. Akt activation results in mammalian target of rapamycin C1 (MTORC1) increases so that the cell cycle regulatory protein namely Cyclin D/E is activated and manifests in the G1/S phase transition to the G2 phase in the cell cycle, causing cell mitosis to undergo [23,[31][32].…”
Section: Discussionmentioning
confidence: 99%